أثر صدمات أسعار النفط على متغيرات السياسة النقدية في الجزائر - دراسة قياسية باستخدام نموذج شعاع الإنحدار الذاتي Var خلال الفترة 1985-2022 - غوال نادية (جامعة الوادي University Of Eloued, 2024)
This study aims to determine the impact of oil price shocks on monetary policy variables in Algeria during the period 1985-2022, using the VAR model The results obtained from this study indicate that there is a relationship between oil price shocks and monetary policy variables, as we found that there is a negative impact on real interest rates and inflation on the one hand, and a positive impact on the real exchange rate on the other hand, and this is reflected in the Algerian economy. Therefore, monetary authorities must adopt appropriate policies in order to absorb various oil shocks.
The impact of oil price shocks on monetary policy variables in Algeria; an econometric study using the VAR model during the period 1985-2022
Keywords: أسعار النفط; السياسة النقدية; الصدمات النفطية; الجزائر; oil prices; monetary policy; oil shocks; VAR mode; Algeria